Prevalence of Refractive Error and Ocular Pathologies among School Children: Finding from the School Eye Program of Dhulikhel Hospital - Shrestha, A.; Shrestha, P.; Shrestha, T.; Makaju Shrestha, R.; Sujakhu, D.; Dhakal, K.; Thapa, G.; Paneru, D. (Kathmandu University Medical Journal, 2021)
Background Childhood blindness and visual impairments could lead to the onset of blindness among children and adolescents. New cases appear particularly between the ages of 6-15 years and if uncorrected, runs a risk of developing Amblyopia, strabismus. There exists a mounting need to strengthen and modify established school eye health programs in Nepal as per the local needs and conditions. Objective To determine the prevalence of refractive error and ocular pathologies among school children in rural Nepal. Method This cross-sectional study was conducted in nine schools of Kavrepalanchowk and Bhaktapur district with 953 students screened from December 2018 to February 2020. The team of optometrist, ophthalmic assistants and ophthalmologist applied a standard protocol for screening of refractive error as a part of the school eye program of Dhulikhel Hospital. Other standard eye examinations were performed to note the ocular pathologies. The association of socio-demographic factors of students having refractive errors with that in emmetropes was identified using logistic regression analysis. Result A total of 953 students were screened in nine study sites, age ranged from 5-19 years. There were 183 students (19.2%) with refractive errors. Blurred vision was the common complaint reported by 2.5% of students. Multivariate logistic regression analysis showed higher age group children (aOR=2.93; 95% CI: 1.62-5.29; P=0.01) and urban area children (aOR=4.37; 95% CI: 0.87-21.98; P=0.07) to have higher odds of refractive error. Conclusion Refractive error is the major eye problem among school children. Despite its high prevalence, there is still a major gap in timely diagnosis and treatment. Regular vision screening and timely treatment is required for better addressing refractive error among school-going children.